GAMBARAN MOTIVASI IBU DALAM PEMBERIAN ASI EKSKLUSIF SELAMA PANDEMI COVID-19 - Novita Dewi; Riri Novayelinda; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
The COVID-19 pandemic has led to the change in the mother’s point of view in exclusive breastfeeding. The aim of this study was to discover the motivation of mother in exclusive breastfeeding during the COVID-19 pandemic. This study used quantitative research with a simple descriptive design that aimed to describe the motivation of mother in exclusive breastfeeding during the COVID-19 pandemic. This study was undertaken in the working area of Inpatient Public Health Center Sidomulyo with a sample size of 71 respondents with a purposive sampling technique by noticing the inclusion criteria. The measuring instrument used was a questionnaire of mother’s motivation in exclusive breastfeeding. The analysis used was univariate analysis. This study indicated that the motivation of mother in exclusive breastfeeding at Inpatient Public Health Center Sidomulyo Pekanbaru had strong motivation, namely as many as 53 people (56.5%), meanwhile respondents who had moderate motivation were 18 people (25.4%). During the COVID-19 pandemic, the mother’s motivation to provide exclusive breastfeeding is very essential in supporting the fulfillment of the physical needs of the baby, particularly for the fulfillment of nutrition and the growth and development of the baby.Keywords: Overview, motivation, exclusive breastfeeding, covid-19